Karakterizacija v romanih Plamenice in solze ter Ženska francoskega poročnika - Spasković, Nastja (Jezik in slovstvo, 2020)
The subjects in postmodern narratives are extremely variable. Although there is no uniform definition that would define their characteristics, Aleid Fokemma offers starting points for their determination. The article discusses questions about the subject in postmodern literature and offers a comparison of the Slovenian postmodern novel Plamenice in solze by Andrej Blatnik and The French Lieutenant's Woman by John Fowles as a starting point for insight into the characteristics of the postmodern literary character.
Keywords: angleška književnost; Blatnik, Andrej; comparative studies; English literature; Fowles, John; postmodern character; postmodernism; postmodernistični subjekt; postmodernizem; primerjalne študije; Slovene literature; slovenska književnost; stereotipi; stereotypes